Mothers’ Perspectives towards Factors Associated with Children’s Screen Time: An Analytical Cross-Sectional Study in the city of Jeddah - Abdulwali, Ruwaydah Abdulrahman; Malibari, Najat Abdullah (Journal of Humanities & Social Sciences, 2025)
This study aimed to identify factors associated with screen time among children in early childhood (ages 3–5) from the perspective of mothers in Jeddah by examining the correlations between parenting styles, household rules regulating children’s screen time, mothers’ attitudes toward children’s screen use, and children’s actual screen time. These factors were selected due to their modifiability, which may help reduce children’s screen time.  The researcher adopted the descriptive method and a cross-sectional analytical design, collecting data through an electronic questionnaire administered to (384) mothers. The instrument comprised four sections: two questions to verify the sample’s suitability to the study population, demographic data, the dependent variable—children’s screen time, and three independent variables (parenting styles, screen-time regulations, and mothers’ attitudes). Results showed a negative correlation between both (the democratic parenting style and screen-time regulations) with children’s screen time, suggesting that democratic practices and clear rules were associated with reduced exposure. By contrast, a positive correlation was found between (the authoritarian style) and children’s screen time, indicating greater exposure. All correlations were weak, except for screen-time regulations, which showed a moderate association. No significant relationship was observed between (mothers’ attitudes or the permissive style) and children’s screen time.  Accordingly, the researcher recommends awareness programs for mothers highlighting the importance of regulating screen use and the role of parenting styles and household rules in reducing exposure. Further research is suggested to investigate additional factors influencing children’s screen-time behavior.
Keywords: Screen time; screen-time regulations; parenting styles; parental modeling; social learning theory